PERUBAHAN PERAN PERGURUAN TINGGI MENJELANG 2O2O - Elvy Maria Manurung (Bina Ekonomi, 2008)
We are facing the knowledge era in 2020. People will dependen on, and rely on their innovation capabilities to continue their lives. Human capabilities  will  increase  (also  their problems  and  requirements become much various and dynamic)  as information  technology  to access ail of information  needed progress.  Boundary of problems become wider, and consequently models become more complex and interdicipline. This point addresses new challenges to the rote of universities. Graduates in this era should see problems and requirement not only from their single-lenses science, but from multi-lenses science, the interconection of one to another. This will help them wider their problems boundaries and consequently will make model more comprehensive and easier to understand. The next step, with comprehensive model, the correction needed can be done. In this era of knowledge, every situation will change. Universities will always be left behind and the graduates will always lack of knowledge.  The situation will become more difficult if they stay in their old way: curriculum revision every s years, or 4 and 3. The main role of universities now is to build scientific way of thinking to stimulate graduates maturity/independency.  They will not be the only producer of knowledge.  They will act as colleagues/partners of knowledge creating.  The university can no longer see themselves as "Maestros". The suitable self-concept for universities now is as entities for broadening boundary of natural science, social science and economy, engineering, and to spread research findings, and to become partner of knowledge creation for industry.